Visual Learning Application in Mathematics Using Holographic Display Based on Multi-touch Technology - Tyng K.S.; Badioze Zaman H.; Mohamad U.H.; Ahmad A. (Springer Science and Business Media Deutschland GmbH, 2023)
Computer aided instruction; E-learning; Engineering education; Holograms; Holographic displays; Learning systems; Education systems; Hologram; Home-based; Malaysian education; Multi-touch technologies; Primary schools; Tablet technology; Teaching and learning; Visual informatics; Visual learning; Students